Implications of the clinical predictive profile of peripheral sensorial neuropathy induced by oxaliplatin for nursing care in cancer of gastrointestinal topography: descriptive observational study (Research, Society and Development, 2020)
Oxaliplatin is a medication used in the treatment of cancer patients, mainly with metastatic rectal colon cancer. However, it can promote the development of Peripheral Sensory Neuropathy (PSN). The objective of this study is to describe the profile of the clinical predictiveness of the development of NSP in patients exposed to Oxaliplatin, to support the safe practice of nursing care in this toxicity. The research was carried out between the months of August 2019 and March 2020, with 29 patients undergoing outpatient chemotherapy treatment at the Adult Chemotherapy Center of Unit I of the National Cancer Institute José Alencar Gomes da Silva, who used Oxaliplatin to treat neoplasia in the topography of the gastrointestinal tract, under the CAPOX and FOLFOX protocols, aged 18 years or over. The prevalence of clinical predictive factors was verified in decreasing order, point to type II diabetes, alcoholism and obesity. The profile of patients who have greater predictive characteristics of the development of PSN induced by Oxaliplatin is female, aged over 60 years and as important as the presentation of comorbidities is the cumulative dose to which they are exposed, sufficient to present neuropathic manifestations in medium dose 780 mg / m². The recognition of predictive factors, the use of instruments to measure the degree of severity of Neuropathy and the description of acute and chronic events can provide support for the management of Oxaliplatin toxicity.